2009
DOI: 10.1128/iai.00227-09
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferi RevA Antigen Binds Host Fibronectin

Abstract: Borrelia burgdorferi, the Lyme disease-causing spirochete, can persistently infect its vertebrate hosts for years. B. burgdorferi is often found associated with host connective tissue, where it interacts with components of the extracellular matrix, including fibronectin. Some years ago, a borrelial surface protein, named BBK32, was identified as a fibronectin-binding protein. However, B. burgdorferi BBK32 mutants are still able to bind fibronectin, indicating that the spirochete possesses additional mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 77 publications
(75 reference statements)
3
107
0
Order By: Relevance
“…The cp32 elements of Lyme disease spirochetes, such as B. burgdorferi, are of particular interest, since they encode Erp, RevA, and Mlp lipoproteins. These bacterial surface proteins are produced by the bacterium during mammalian infection, and those with known functions serve as adhesins for host components, such as plasmin(ogen), laminin, and complement factor H (1,7,8,9,10,13,22,25,26,32,33,38,42,43,49,63). Sequences of the erp, revA, and mlp loci generally vary between different cp32s (Fig.…”
mentioning
confidence: 99%
“…The cp32 elements of Lyme disease spirochetes, such as B. burgdorferi, are of particular interest, since they encode Erp, RevA, and Mlp lipoproteins. These bacterial surface proteins are produced by the bacterium during mammalian infection, and those with known functions serve as adhesins for host components, such as plasmin(ogen), laminin, and complement factor H (1,7,8,9,10,13,22,25,26,32,33,38,42,43,49,63). Sequences of the erp, revA, and mlp loci generally vary between different cp32s (Fig.…”
mentioning
confidence: 99%
“…An examination of the paradigm for reciprocal regulation of ospA and ospC revealed that the heterogeneous expression of OspA and OspC by spirochete populations during the tick blood meal results from the intricate order of transcriptional and translational changes that ensue as B. burgdorferi transitions between the vector tick and mammalian host (8). Brisette et al found that also RevA is produced during mammalian infection but not during colonisation of vector ticks (9). A proteome study demonstrated that the response of B. burgdorferi to changing in vitro culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions of B. burgdorferi with fibronectin are facilitated by several distinct bacterial surface proteins, including BBK32, RevA, BB0347, and CspA (BbCRASP-1) (28)(29)(30)(31). The redundancy in adhesins makes it difficult to dissect the role of each B. burgdorferi fibronectin binding protein in the pathogenesis of Lyme disease.…”
mentioning
confidence: 99%
“…RevA expression is elevated during mammalian infection over its expression in the tick vector, suggesting a role in pathogenesis (30,(34)(35)(36). RevA binds to fibronectin, and anti-RevA antibodies block the binding of whole B. burgdorferi bacteria to fibronectin (30).…”
mentioning
confidence: 99%